Acusilau d' Argos i els primers mitògrafs: entre oralitat i esriptura - Pàmias i Massana, Jordi (Faventia, 2008)
Diffusion of alphabetic writing had long-lasting effects on the construction and transmission of memory in Greece, as fragments from Hecataeus of Miletus or Pherecydes of Athens show. Yet conceptions of literacy in early mythographers are rather problematic, as Acusilaus’ test. 1 suggests, which encourages understanding the relationship between orality and literacy in non-developmental terms.